DETERMINAN KEJADIAN OBESITAS PADA REMAJA SEBAGAI FAKTOR RISIKO PENYAKIT TIDAK MENULAR - Nopianto Nopianto; Kartini Kartini; Hendri Parluhitan L.Tobing; Lestari Rahmah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Obesity is a condition characterized by excessive accumulation of body fat resulting from a long-term imbalance between energy intake and energy expenditure. Obesity has various negative health effects, both in the short and long term. The purpose of this study was to identify the determinants of obesity among adolescents as a risk factor for noncommunicable diseases. This study employed a cross-sectional design. The study was conducted at a high school in Dumai City in September 2025. The sample consisted of 70 participants. Stratified random sampling was used. The research instrument consisted of a questionnaire. Data analysis was performed using univariate and bivariate methods. The results indicated an association between dietary patterns (p-value: 0.047) and physical activity (p-value: 0.040) and the prevalence of obesity among adolescents. It is recommended that schools organize educational programs on healthy eating habits and the impacts of obesity, involving nutritionists, and implement healthy cafeteria policies that provide balanced and nutritious meals. Sports facilities should be improved, and students should be encouraged to be more active through extracurricular activities and regular sports events.Keywords: Physical Activity, Dietary Patterns, Adolescents.